The impact of a computerized decision aid on empowering pregnant women for choosing vaginal versus cesarean section delivery: study protocol for a randomized controlled trial - Eslami, Saeid (Trials, 2015)
BACKGROUND: Cesarean delivery on maternal request (CDMR) is one of the main reasons for cesarean delivery in Iran, and women often need help in making a decision about the delivery options available to them. The main objective of this study is to evaluate the effect of a computerized decision aid (CDA) system on empowering pregnant women in choosing an appropriate mode of delivery. This CDA contrasts the advantages and disadvantages of vaginal versus cesarean section delivery in terms of their value to the individual woman. METHODS/DESIGN: The protocol concerns a randomized trial study that will be performed among Iranian women. Four hundred pregnant women will be recruited from two private and two public prenatal centers in Mashhad, Iran. They will be randomly assigned to either an intervention or a control group. The designed CDA will be provided to the intervention group, whereas the control group will only receive routine care. The CDA provides educational contents as well as some recommendations. The CDA’s knowledge base is obtained from the results of studies on predictors of cesarean delivery. The CDA’s software will be installed on women’s computers for use at home. The two primary outcomes for the study are O’Connor’s Decisional Conflict Scale and knowledge as measured by true/false questions. Actual mode of delivery (vaginal versus cesarean) will be compared in the two groups. DISCUSSION: We investigate the effect of a CDA on empowering pregnant women in terms of reducing their decisional conflict as well as on improving their clinical knowledge pertaining to mode of delivery. TRIAL REGISTRATION: This trial is registered with the Iran Trial Registrar under registration number IRCT2015093010777N4 and registration date 26 October 2015.